Mobile athlete self-report measures and the complexities of implementation - Duignan, C. M.; Slevin, P. J.; Caulfield, B. M.; Blake, C. (Journal of Sports Science & Medicine, 2019)
Recent practice in athlete monitoring has seen the development and implementation of customized, digital Athlete Self-Report Measures or Mobile Athlete Self-Report Measures (M-ASRM) across various sport settings, including amateur sports such as Gaelic Games. Successful implementation of M-ASRM requires significant consideration of the use context and limitations therein, an investment of time and expertise by staff and buy-in from key stakeholders, yet there is limited evidence of these considerations being applied in practice. This study aimed to investigate stakeholder perceptions regarding the implementation processes and understanding of a pre-existing M-ASRM in elite Gaelic Games. Semi-structured interviews were conducted with the use of a topic guide to explore the rationale, introduction and use of M-ASRM. Participants were 21 M-ASRM users in elite Gaelic Games (players n = 10, coaches and support staff n = 11), from 15 teams. Thematic analysis was conducted collaboratively by two authors, adopting an inductive approach and coding the transcripts using NVivo 12 software. Four higher-order themes were formed from the data: (1) clarity of purpose; (2) implementation strategies; (3) players perceptions of use and (4) perceived facilitators of M-ASRM use. The results of this study demonstrate a significant underestimation of the practical requirements for successful implementation of an M-ASRM by users in elite Gaelic Games. Recommendations are made for implementation and best practice use, including shared decision-making, evidence-based education strategies, structured feedback channels and improved planning with regards to feasibility and responsibility.